Waste electric and electronic equipment (WEEE) management: A study on the Brazilian recycling routes. (10th February 2018) - Dias, Pablo; Machado, Arthur; Huda, Nazmul; Bernardes, Andréa Moura
Abstract: Processing of waste electric and electronic equipment (WEEE) is a growing issue and a worldwide challenge due to an enormously large volume of WEEE being generated around the world. WEEE typically contains valuable and precious materials in addition to some hazardous components, which could potentially lead to economic and environmental benefit if recycled properly. In Brazil, the WEEE generation has significantly increased in the past decade and the best process routes to recycle it remain little explored. This study shows a systematic analysis of WEEE processing procedures based on the information found and mapped from 134 recycling companies active in Brazil by contacting them and confirming activity. It was found that in spite of the recent implementation of national waste management policies, federal and local government do not have control over the number of active WEEE recycling companies in the country. It was possible to explain the role of the different agents in the Brazilian recycling scenario. Moreover, this study shows that 89% of the Brazilian recycling companies only undertake the pretreatment phase in the recycling process – sorting and dismantling - and that at least 92% dismantle WEEE manually. Finally, it is shown that WEEE that is more complex to recycle is still being shipped abroad for foreign downstream companies and that the revenue generated by the WEEE recycling market in Brazil can financially support up to five agents involved in the WEEE flow. Graphical abstract: Image 1 Highlights: 134 recycling facilities in Brazil were mapped and their activity was confirmed. WEEE flow in Brazil is explained and agents involved are described. Brazilian WEEE recyclers only undertake initial recycling. Majority of Brazilian WEEE recycling facilities dismantle WEEE manually. WEEE recycling market in Brazil can financially support up to 5 agents involved.